Self-Reliance, Determination and Home-Attachment in Lutfiya Al-Dulaymi’s Hayat’s Garden - Mahmoud, Amel (Humanities Journal of University of Zakho, 2022)
This present research deals with the novel Hadiqat Hayat, Hayat’s Garden, (2003) by the Iraqi female author Lutfiya Al-Dulaymi (1939 - ). The discussion focuses on the struggles the main character Hayat undergoes while confronting the debilitating circumstances of the wars and the anguish of waiting for the absent husband. While analyzing the character of the protagonist, Hayat, specific features are illustrated and highlighted such as; her self-reliance and independence, firm resolution to overcome difficulties, and her strong attachment to her house specifically her garden. The personality of the single mother, which is caught in the protagonist Hayat, breaks the stereotypical image of the helpless widow as it reveals a strong character capable of conquering the social restrains and the economic challenges with her inner vigor, determination and optimistic soul. On the symbolic level, Hayat gains another dimension of reference through her name, which means life. In this way, she becomes an embodiment of the country, Iraq, itself while confronting the calamities of wars symbolizing its survival and its continuity.